3D kinematic and dynamic analysis of diagonal stride in elite backcountry skiing (SKIALP) and cross-country skiers - Pozzo, R.; Canclini, A.; Canclini, A.; Baroni, G. (Science and Skiing VII, 2018)
In recent years, backcountry skiing (SKIALP) has become more and more popular, and SKIALP skiers have improved their technical and physiological performances. Due to the complex and multiparametric conditions (e.g., air and snow temperatures, track, technique, weight of equipment) which induce significant changes in the biomechanical constraints of the skiers` movements and the relatively recent development of the discipline, there is a lack of specific studies especially under race conditions (Pozzo, 2015). On the other hand, technique analysis on elite crosscountry (XC) skiers and comparisons between normal races and treadmill conditions have been undertaken (Canclini, 2007; Due, 2011; Haselbacher, 2014; Halonen, 2015; Tosi, 2009). The purpose of this study was to compare the kinematic and dynamic patterns of elite SKIALP and XC skiers under simulated competition conditions.